2016
DOI: 10.1007/s40261-016-0388-9
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life During Routine Treatment with the SQ-Standardised Grass Allergy Immunotherapy Tablet: A Non-Interventional Observational Study

Abstract: Background and ObjectiveAllergy immunotherapy (AIT) with the SQ® grass sublingual immunotherapy (SLIT)-tablet has been shown to be efficacious, well-tolerated and to improve disease-specific health-related quality of life (HRQoL) in controlled clinical trials. The aim of our study was to investigate HRQoL in patients with allergic rhinoconjunctivitis routinely treated with the SLIT-tablet and taking symptomatic medication as needed compared with patients treated only with symptomatic medication.MethodsIn a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…They concluded that although improvements in QoL were noted in both groups, changes in overall scores and the majority of domains only achieved statistical significance in the SCIT group. Some other non-interventional studies have also evaluated improvements in QoL in patients with AR, focusing only in SLIT treatments, and showing also positive results (23,24,41). Interestingly, in the study published by Horn (24), routine treatment with a grass SLIT-tablet resulted in clear improvements in disease-specific and general quality of life, while no improvements were observed in patients treated only symptomatically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that although improvements in QoL were noted in both groups, changes in overall scores and the majority of domains only achieved statistical significance in the SCIT group. Some other non-interventional studies have also evaluated improvements in QoL in patients with AR, focusing only in SLIT treatments, and showing also positive results (23,24,41). Interestingly, in the study published by Horn (24), routine treatment with a grass SLIT-tablet resulted in clear improvements in disease-specific and general quality of life, while no improvements were observed in patients treated only symptomatically.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a number of studies with AIT have been reported, where the improvement in HRQoL is evaluated mostly as a secondary efficacy variable (19,20,21,22). These studies had shown positive results in HRQoL, but most are clinical trials with sublingual immunotherapy (SLIT), and data from real life studies are still scarce (23,24). Therefore, there is still a need for more clinical evidence, specially with non-interventional studies, where a higher representation of patient's population can be included, as children, patients with comorbidities, etc.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Data on assessments of dissatisfaction with symptomatic medication in patients with allergic rhinoconjunctivitis have been reported previously [31,32]. In a non-interventional, observational study involving patients treated routinely with the SQ Ò grass SLIT-tablet and symptomatic medication as needed, and patients treated only with symptomatic medication, disease-specific and general health-related quality of life were observed to improve markedly during the GPS compared with the previous GPS before the start of treatment in those patients receiving the SQ Ò grass SLIT-tablet, while patients treated only by symptomatic medication without AIT showed no improvement [25].…”
Section: Discussionmentioning
confidence: 98%
“…The SQ Ò -standardised grass sublingual immunotherapy (SLIT)-tablet contains a fast-dissolving extract of Phleum pratense (timothy grass; GRAZAX Ò ; ALK, Hørsholm, Denmark), which is indicated for the disease-modifying treatment of grass pollen-induced rhinitis and conjunctivitis in adults and children (5 years and older). The tolerability and efficacy of the tablet, including long-term efficacy and disease-modifying effect, has been demonstrated in several randomized controlled trials (RCTs) in Europe and USA [8][9][10][11][12][13][14][15][16][17][18][19][20], and tolerability in adults and children, health-related quality of life and feasibility of intra-seasonal start of treatment in real life have been documented in several non-interventional observational studies [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The safety, tolerability, data on adherence, effectiveness and health-related quality of life have been investigated in several non-interventional, observational studies with the SQ Ò grass SLIT tablet in real-life application by allergists in Germany, including a study on intra-seasonal initiation of treatment with more than 600 patients [19][20][21][22] that confirmed results from a previous Randomized double-blind placebo-control (RDBPC) trial [18]. A cohort study, including all German National Health beneficiaries insured by the German health insurance provider AOK PLUS (Saxony) from 2005 to 2011, revealed a proportion of 36.2% of adult patients with allergic rhinitis treated exclusively by general practitioners, and a proportion of 21.2% of children [23].…”
Section: Introductionmentioning
confidence: 99%